Commodities at a Glance: Special Issue on Food Security - United Nations Conference on Trade; Development (United Nations, 2016)
The series “Commodities at a Glance” aims to collect, present and disseminate accurate and relevant statistical information linked to international primary commodity markets in a clear, concise and reader-friendly format. This issue of Commodities at a Glance focuses on the global food security, price volatility and continuing high food prices.